(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Sexual violence is one of the morbidities and mortality factors in women. Sexual violence of women causes physical and physiological sequences that make them vulnerable to health problems. Material and method: It was normative legal research with a literature study and document study as a method to collect the research data. Findings: Marital sexual abuse or the highest personal relation was incest with 1,071 cases followed by raping with 818 cases, and molestation with 321 cases. Meanwhile, marital rape reached 195 cases. The forms of sexual violence consist of sexual harassment, sexual exploitation, coercion of contraceptive use, compulsion in abortion, rape, marital compulsion, prostitution, sexual bondage, and sexual torture. The protection against victims of sexual violence was considered to be not optimal due to a lack of public understanding of the causes and effects of sexual violence. Conclusion: So far, the legal protection against women in sexual violence cases have not been optimally implemented. The minimum legal protection triggered impunity, reoccurrence, and even the victims’ frustration to accept justice and recovery.